27.36+0.7x=-6.4(x+4.6)

Simple and best practice solution for 27.36+0.7x=-6.4(x+4.6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27.36+0.7x=-6.4(x+4.6) equation:



27.36+0.7x=-6.4(x+4.6)
We move all terms to the left:
27.36+0.7x-(-6.4(x+4.6))=0
We calculate terms in parentheses: -(-6.4(x+4.6)), so:
-6.4(x+4.6)
We multiply parentheses
-6.4x-29.44
Back to the equation:
-(-6.4x-29.44)
We get rid of parentheses
0.7x+6.4x+29.44+27.36=0
We add all the numbers together, and all the variables
7.1x+56.8=0
We move all terms containing x to the left, all other terms to the right
7.1x=-56.8
x=-56.8/7.1
x=-8

See similar equations:

| 31x/31=-4/31 | | 5x,x=6 | | |3x+4|=|6x-4| | | 17x-7-3=24 | | 2,000=10x | | 6+8x=2.5x | | 27.36+0.7x=-6.4(x+4.6 | | x^2-30+33=0 | | -3k+4+4k=14-21 | | 8(3a+6)=9( | | −18−n=−9 | | y/6+13=18 | | 106=3v | | 9-2r=25 | | -5(4-x)-x=28 | | 27,36+0.7x=-6.4(x+4.6 | | -140=20b | | n7+5=−2 | | 3(3x-4-7=8 | | 11t=265 | | x+4-2=8 | | -29=-20+w | | 2x²+6x-10=0 | | 9(n+1)=2(n-1 | | 2(x+4)+3x+2=20 | | 54=d/2 | | 7/8-1/2=3/16m+5 | | 69=9k+4(k+1) | | P-0.5p=150 | | 80+t10=50 | | 6n+5(-6n+1)=173 | | 3(u-4)-8u=-17 |

Equations solver categories